Correlation of Sol–Gel Alumina-Supported Cobalt Catalyst Processing to Cobalt Speciation, Ethanol Steam Reforming Activity, and Stability - Passos, Aline R. [UNESP]; Martins, Leandro [UNESP]; Pulcinelli, Sandra H. [UNESP]; Santilli, Celso V. [UNESP]; Briois, Valérie (Wiley, 2017)
The effect of sol–gel alumina characteristics on the supported Co catalyst properties was investigated at the different steps of catalyst preparation. Porous alumina with variable surface reactivity were prepared from the sol–gel transition and the spinodal decomposition induced by polymers. The hydrophobicity of polymer or the calcination temperature controls the amount of the hydroxyl groups. The dried catalysts are composed of cobalt alumina hydrotalcite-like compounds up to 64 %. After calcination, higher proportions of CoAl2O4 are observed in the alumina presenting a greater content of hydroxyl and hydrotalcite. The Co speciation during activation investigated by Quick X-ray absorption spectroscopy evidences that both Co3O4 and CoAl2O4 are first fully reduced to CoO and then partially transformed into point-like Co0 nucleus. The catalysts were highly active in the ethanol steam reforming reaction; however, coke deposition leads to deactivation. This deleterious effect was minimized for catalysts operating with a CoO/Co0 ratio close to 1:3.
Keywords: aluminum; cobalt; supported catalysts; surface analysis; X-ray absorption spectroscopy